MODEL OF THE OPTIMUM EXCHANGE RATE - Vladimir P. Semenov; Yuriy P. Soloviev; Evgeniya V. Gorshkova (Вестник Российского экономического университета имени Г. В. Плеханова)
During 25 years of designing and developing market economy in Russia well-balanced tools of shaping currency rate, which is adequate to the economic situation in the country has not been formed. The ruble rate to world reserve currencies controlled by Russian management always had certain signs of voluntarism, it was fixed without due regard to ruble inflation rate. It finally led to severe finance and currency crises of 1998, 2008, 2014. The article proposes economically substantiated model of optimum currency rate. It provides calculations showing efficiency of the tools and supporting the final conclusion: long-term shaping of currency rate asynchronous to the inflation rate is a forerunner of the next finance crisis.